The Effect of Leadership Style and Human Resource Quality on Work Performance: Motivation As A Mediation Variable - Ridwan, Muhammad; Mulyani, Sitti Rizki; Putra, Rio Andhika; Brama Kumbara, Vicky (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2025)
This study examines the influence of leadership style and human resources on work performance and employee motivation as a mediation variable at PT. Teluk Luas Padang. Primary data was obtained by administering questionnaires directly to respondents who are PT Teluk Luas Padang employees. Data analysis in this study used validity, reliability, classical assumption test (data normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, Path Analysis, determinant coefficient (R2), partial regression coefficient (t-test), the regression coefficients together (F-test), while the overall data analysis uses SPSS statistic 16 software. The results of this study conclude that (1) leadership style significantly affects work performance. (2) human resources have a significant effect on work performance. (3) work motivation has no significant effect on work performance. (4) leadership style has no significant effect on work performance through work motivation. (5) human resources significantly affect work performance through work motivation. (6) leadership style and human resources simultaneously significantly affect work performance. (7) leadership style and human resources simultaneously significantly affect work performance through work motivation.